The Eldritch Portal : an analysis of ludonarrative immersion & user experience in interactive weird fiction : an exegesis presented in partial fulfilment of the requirements for the degree of Master of Creative Enterprise at Massey University, Wellington, New Zealand - Knight-Devlin, Liam Patrick Colin (Massey University, 2021)
This research exegesis functions as a companion piece that contextualises the principles expressed within the creative work, ‘Project: Mystic’. In this research I contend that the role of user experience design has not been closely studied or documented when discussing the relationship between atmospheric spatial design and ludonarrative principles inside interactive digital environments. The purpose and aim of this research is to determine how the aesthetics of atmosphere influence the principles of ludonarrative immersion and user experience design in the context of weird fiction and the sublime. Using a pragmatic methodological approach I use interactive demonstrations accompanied with qualitative surveys to determine the effectiveness of atmosphere design in a players experience and engagement. Using these results I form a discussion around the concepts of aesthetic experiences, non-euclidean narratives, and Burke’s notions of sublimity and the role of the ‘Deity’ figure in weird fiction.
Keywords: aesthetics; atmosphere; immersion; ludonarrative; user experience; weird fiction; 330310 Interaction and experience design